HAK DAN KADAR NAFKAH ISTERI DALAM PERSPEKTIF KHI DAN IMAM AN-NAWAWI DALAM KITAB AL-MAJMU’ SYARAH AL-MUHADZDZAB - Siti Fatimatul Muffidah; Ash-Shabah, Musyaffa Amin; Suprihatin; Supriyanto, Agus (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2025)
The increase in divorce rates in Indonesia is primarily triggered by economic problems and the inability of husbands to fulfill their wives' rights and provide for them in domestic life. This study compares the rights of wives and the level of provision in the Compilation of Islamic Law (KHI) and the book al-Majmu' Syarah al-Muhadzdzab by Imam An-Nawawi. This study is a normative comparative study. The results show that both the Compilation of Islamic Law (KHI) and Al-Majmu' Syarah al-Muhadzdzab share the basic principle that the husband's obligation to provide financial support depends on his economic ability and applies after the wife shows tamkin. Both sources of law emphasize that a wife who is in a state of nusyuz loses her right to financial support. The main difference lies in the normative and contextual aspects; Al-Majmu' provides quantitative details of maintenance based on the husband's financial condition, such as two mud for a well-off husband, one mud for a husband in difficulty, and one and a half mud for a husband in between. Meanwhile, KHI is more flexible, accommodating adjustments to Indonesia's socio-economic conditions by providing space for practices that are in line with the dynamics of a more diverse society. Overall, this study contributes to the integration of classical fiqh and positive Islamic law in Indonesia, while offering a theoretical and practical foundation for the development of a fair, contextual, and public-interest-oriented family law